Hall of the Oneg Shabbat and Gemilut Hasadim Society - Putnik-Prica Vladana; Dautović Vuk (Nasleđe)
The interwar period was an extremely important time for the process of Jewish emancipation and integration into Serbian society, in which Belgrade's Jewish community played a leading role. The construction of the buildings of the Union of Jewish Municipalities and the Oneg Shabbat and Gemilut Hasadim charitable society in 1923 marked the beginning of the construction of the key landmarks of Jewish religious, cultural and political life in the capital of the newly formed Kingdom of Serbs, Croats and Slovenes. The construction of the Sukkat Shalom Ashkenazi synagogue was also completed in this period, with the Memorial to Jewish soldiers who died in the Balkans and the First World War at the Jewish Sephardic cemetery in Belgrade and the construction of the monumental hall of the Jewish Church-School Community having also been completed by the end of the 1920s. The building of the Oneg Shabbat and Gemilut Hasadim Society, designed by architect Samuel Sumbul, represents an extraordinary example of the use of Orientalist motifs in architecture, the goal of which was the public representation of the Jewish community in Belgrade. The intention of this paper is to investigate the context of the creation of the project in greater detail, highlight its stylistic models and parallels, and to further draw attention to the role of architecture in the service of public visual representation of Jewish religious and ethnic identities in Belgrade.